UPAYA PENCEGAHAN DAN PENANGGULANGAN DAMPAK PEMANASAN GLOBAL - Nawa Suwedi (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2005)
Global warming can be influented by natural and human activities. Effect andimpact of it should be consider for all countries of the world . To reduce the global warming effects some activities will be shown in this paper. They will be divided into prevention and tackling activities.